Direct CO2 photoreduction from flue gas by synergistic catalysis of a nickel metal–organic framework and a ruthenium polypyridyl complex. Issue 4 (12th January 2023) - Dong, Man; Tian, Yu; Gu, Jian-Xia; Wang, Xiao-Hui; Wang, Lin-Xin; Hou, Bao-Shan; Yousuf, Afifa; Sun, Chun-Yi; Wu, Jie; Kang, Zhen-Hui; Wang, Xin-Long; Su, Zhong-Min
Abstract : A CO2 bridged photocatalytic interface between a nickel metal–organic framework and ruthenium pyridine for high-efficiency photoreduction of diluted CO2 . Abstract : Direct photoreduction of CO2 from flue gas is an energy-saving avenue to realize the carbon-neutral cycle but it is still in its infancy. Herein, we constructed a new anionic metal–organic framework based on trinuclear Ni clusters and thiophenecarboxylic acid for CO2 photoreduction of exhaust gas from a power plant. Under visible-light irradiation, the yield of CO was 17.4–26.3 mmol g −1 in diluted CO2 with a concentration of 5–20%. The apparent quantum yield (A.Q.Y.) under a 10% CO2 atmosphere was determined to be 2.1%, which ranks among the highest values of the reported photocatalysts under similar conditions. Importantly, in real flue gas containing 10% CO2, a selectivity of 90.4% was achieved and CO generation reached 18.2 mmol g −1 . In situ transient photovoltage (TPV) and density functional theory (DFT) calculations showed that the formation of a CO2 bridged photocatalytic interface between Ni-MOF1 and a Ru complex ([Ru(bpy)3 ]Cl2 /[Ru(bpy)2 ]Cl2 ) was a crucial factor for the efficient CO2 -to-CO conversion in diluted CO2 .